Effect of Carrageenan Addition to the Edible Characteristics of Tilapia Skin Gelatin Film (Oreochromis niloticus) - Anjar Setyaji; Ima Wijayanti; Romadhon Romadhon (Program Studi Teknologi Pangan, 2018)
Gelatin of skin tilapia (Oreochromis niloticus) has the potential as an edible film but has weaknesses due to the hydrophilic so that the value of the water vapor transmission rate is high. The addition of carrageenan combined with palmitic acid is used to improve the characteristics of edible films modified bythe polymer network so that it can act as cross linking which is expected to reduce the rate of water vapor transmission rate edible film. indigo and get the best carrageenan concentration edible film seen from the value of the water vapor transmission rate. The ingredients used are tilapia skin gelatin, carrageenan and palmitic acid. The research method used was experimental laboratories with completely randomized design (CRD) experimental design. Parameters observed were thickness test, solubility, tensile strength, percent elongation and water vapor transmission rate. Data were analyzed using variance analysis (ANOVA). To find out the differences between treatments, the data was tested by HSD further tests. The results showed that the difference in carrageenan concentration significantly affected (P<0,05) the thickness value, tensile strength, percent elongation, solubility and water vapor transmission rate. Addition of carrageenan 0.8% was the best result which has a tensile strength of 4.209 ± 0.241 MPa, elongation percent 16.332 ± 1.019%, solubility of 65.911 ± 2.930% and water vapor transmission rate of 7.792 ± 0.376 g / m2. Hour. Testing of tensile strength in 0,8% carrageenan film showed that the film matrix binds so that the film was not easily broken compared to the control. The low water vapor transmission rate in the 0.8% carrageenan addition edible film sample showed the formation of cross linking between gelatin and carrageenan protein molecules.